2019
DOI: 10.22435/mpk.v29i3.1293
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Penghambatan α-glukosidase dan Peredaman Radikal Bebas Ekstrak Kapang Endofit yang Diisolasi dari Rimpang Kunyit

Abstract: Abstract Diabetes mellitus is one of the metabolic disorders that causes an increase in blood sugar levels above normal the normal threshold. The case of diabetes is usually accompanied by an increase in free radicals in the patient’s body. In Indonesia, one of the plants traditionally used to treat high blood sugar levels and contains antioxidant compounds is turmeric. The use of endophytic fungi from medicinal plants as a source of active compounds is widely carried out. Therefore this research aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The activity of some endophytic fungi from the other tissues of the turmeric plant has also been previously reported. Ethyl acetate extract of endophytic fungi of Bo.Ci.Cl.R5 isolated from turmeric rhizome tissue had an antioxidant activity with IC 50 values of 91.70 µg/ml (Septiana et al, 2019a). Likewise, ethyl acetate extract of endophytic fungi of Bo.Ci.Cl.A3 and Bo.Ci.Cl.D1 isolated from the root and leaf tissue of turmeric plant had an antioxidant activity with IC 50 values of 75.71 and 24.04 µg/ml respectively (Septiana & Simanjuntak, 2017;Septiana et al, 2019b).…”
Section: Antioxidant Activity Testmentioning
confidence: 97%
See 1 more Smart Citation
“…The activity of some endophytic fungi from the other tissues of the turmeric plant has also been previously reported. Ethyl acetate extract of endophytic fungi of Bo.Ci.Cl.R5 isolated from turmeric rhizome tissue had an antioxidant activity with IC 50 values of 91.70 µg/ml (Septiana et al, 2019a). Likewise, ethyl acetate extract of endophytic fungi of Bo.Ci.Cl.A3 and Bo.Ci.Cl.D1 isolated from the root and leaf tissue of turmeric plant had an antioxidant activity with IC 50 values of 75.71 and 24.04 µg/ml respectively (Septiana & Simanjuntak, 2017;Septiana et al, 2019b).…”
Section: Antioxidant Activity Testmentioning
confidence: 97%
“…Endophytic fungi are one of the endophytic microbes that live in the tissues of their host plants without causing symptoms of a disease, living in symbiotic mutualism with their hosts by producing secondary metabolites (Nicoletti & Fiorentino, 2015). Previous studies reported that endophytic fungi from rhizomes and leaves of turmeric have antioxidant activity (Septiana et al, 2019a;Septiana et al, 2019b). However, there are no studies that report the endophytic fungi from turmeric flowers to have antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungi isolated from various tissues of turmeric have also been shown to have antioxidant properties. Endophytic fungi extracts from turmeric rhizome, root, leaves, and also turmeric stem, exhibited antioxidant activity in ethyl acetate (Widowati et al 2016;Eris & Simanjuntak 2017;Septiana et al 2019;Septiana et al 2020). Chrisonilia sitophila, Acremonium sp., and Penicillium sp.…”
Section: Indonesia Medicinal Plant Endophytic Fungi Produced Antioxidantmentioning
confidence: 99%